Determinanty niezależności banku centralnego w krajach transformacji - Pietrucha, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper discusses the determinants of central bank independence in transition countries. The first part of this paper reviews the determinants of central bank autonomy. The second part contains some evidence from transition countries. Only progress in transition (mean of EBRD transition indicators) is significant in explaining independence of central bank in transition countries. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 444-453